Merawat Sejarah: Meningkatkan Pengetahuan Masyarakat Islam Dalam Memaknai Isra Mikraj Nabi Muhammad Saw - M. Dien Madjid (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
Isra Mi'raj is an event that occurred directly by the Prophet Muhammad SAW. This was in order to comfort the Prophet Muhammad SAW who was left behind by two people he loved very much, namely Khadijah (wife) and Abdul Tholib (Uncle). In addition, the Isra Mi'raj event is a form of spiritual journey given by Allah to the Prophet Muhammad SAW to meet Allah directly and receive the order to pray. This event is a form of Muslim belief in the Prophet Muhammad SAW, and believes in the orders given by Allah. This research method is library research by analyzing primary sources such as books, journal articles and books related to the event. While the secondary sources in this study, namely books related to the theme as a support in this study. The results of this study can be concluded, that the Isra Mi'raj Celebration is not only an important event in Islam but also has a significant impact on the social and cultural life of the Muslim community. The role of the Islamic community in interpreting Isra Mi'raj also reflects the diversity of traditions and religious practices that exist in various regions. From shadow puppet shows in Java to Quran recitations in Aceh, each community presents a unique interpretation in accordance with cultural heritage and local wisdom. This shows that the Isra Mi'raj celebration is not only a worship ceremony, but also a manifestation of the diversity and cultural richness inherent in Islamic society in the archipelago.